A low-complexity explicit MPC controller for AFR control. (September 2015) - Honek, Marek; Kvasnica, Michal; Szűcs, Alexander; Šimončič, Peter; Fikar, Miroslav; Rohal'-Ilkiv, Boris
Abstract: Control of the air–fuel ratio in combustion engines is of imminent importance when aiming at reduction of the fuel consumption and mitigation of emissions. In this paper this is achieved by employing Model Predictive Control (MPC), which keeps the air-fuel ratio close to the stoichiometric value. The real-time implementation of MPC is accelerated by pre-computing the optimal solution and using the explicit MPC approach. The memory footprint of such a controller is subsequently reduced by employing a two-layered compression scheme. Quality of the regulation is demonstrated using real engine data and is compared to traditional control approach based on PID. Abstract : Highlights: Design of explicit model predictive controller for air/fuel ratio. Tested on the real combustion engine. Reduction of explicit model predictive controller memory footprint. Employment of two-layered compression scheme.